2016
DOI: 10.1177/0898010116655004
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Spiritual Well-Being in Nursing Students: A Cross-Sectional Study

Abstract: Higher scores of SWBS and importance given to religiosity were related to lower scores of BAI. Also, the performance and score of spiritual well-being were related to anxiety scores. Further research is worthy to identify and validate which educational aspects could promote spiritual well-being and reduce anxiety as well as research to analyze the relation between spiritual well-being score and learning outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
(28 reference statements)
2
14
0
Order By: Relevance
“…2 The use of alcohol and cocaine, on its turn, was not associated with academic performance among the participants of this study, diverging from other studies conducted with students. 4,8,18,24 In this regard, it is also worth mentioning some controversial results from previous studies that sometimes point to the use of alcohol as a predictor of low academic performance, 8,18,24 and other times point individuals with high performance as more susceptible to higher use of alcohol. 4 In spite of these controversies, studies on drug use and performance, in their majority, 2-3,5-7,23-24 provide important recommendations related to drug prevention strategies in universities and/or schools, which are reiterated by this study considering the high prevalence of marijuana use in the sample studied.…”
Section: /10mentioning
confidence: 98%
See 2 more Smart Citations
“…2 The use of alcohol and cocaine, on its turn, was not associated with academic performance among the participants of this study, diverging from other studies conducted with students. 4,8,18,24 In this regard, it is also worth mentioning some controversial results from previous studies that sometimes point to the use of alcohol as a predictor of low academic performance, 8,18,24 and other times point individuals with high performance as more susceptible to higher use of alcohol. 4 In spite of these controversies, studies on drug use and performance, in their majority, 2-3,5-7,23-24 provide important recommendations related to drug prevention strategies in universities and/or schools, which are reiterated by this study considering the high prevalence of marijuana use in the sample studied.…”
Section: /10mentioning
confidence: 98%
“…As for the year, it is suggested that first year students see the adaptation phase to the course and the university environment as an additional challenge to the demands of the course. 4,[26][27] Regarding the area of the course, it is understood that the courses in the health area tend to adopt more traditional evaluation strategies, as well as a practical internship that requires the student to exercise different professional skills and that may interfere in the student's self-evaluation. Further studies are recommended using other variables, as well as a more appropriate collection tool to analyze this question deeply.…”
Section: /10mentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of quantitative studies about this theme (1)(2)(3)(4)(5)(6)(7)(8)(12)(13)(14)(15)(16)(17)(18) . However, this research offers subsidies based on a qualitative perspective, from the perception of student leaders, broadening this discussion.…”
Section: Objectivementioning
confidence: 99%
“…The adaptation to a new routine, on the other hand, is a critical moment of transformations in an individual's lifestyle, support network and autonomy. Thus, the requirements of this stage of life can lead to greater vulnerability to the adoption of harmful behaviors and to possible fluctuations in their psychological well-being (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%